Behavioral Mediators of the Association between Neighborhood Environment and Weight Status in Nigerian Adults. Issue 1 (September 2013) - Oyeyemi, Adewale L.; Deforche, Benedicte; Sallis, James F.; De Bourdeaudhuij, Ilse; Van Dyck, Delfien
Purpose: Neighborhood built environments are related to obesity and physical activity (PA), but inconsistently to sedentary behaviors. This study investigated the mediating effects of PA and sedentary time on the associations of neighborhood environmental factors and body mass index (BMI) among Nigerian adults. Design: The study design was cross-sectional. Setting: The study setting was metropolitan Maiduguri, Nigeria. Subjects: Nigerian adults (n = 1411) were randomly selected from diverse neighborhoods and had complete data (43.1% women, 33.8% overweight or obese). Measures: PA, sedentary time, and 16 perceived neighborhood environmental factors were measured using Nigerian adaptations of validated international questionnaires. Outcomes were measured BMI and interviewer-led self-reports of moderate to vigorous PA, walking, total PA, and sitting time. Analysis: The product-of-coefficient test using generalized linear models was used to assess the mediating effects of outcomes on the associations between environmental factors and BMI. Results: Walking and total PA significantly mediated the association between BMI and perception of higher residential density (αβ = –.025 and –.037, respectively), absence of garbage (αβ = –.046 and –.076, respectively), and more safety from crime at night (αβ = –.044 and –.083, respectively). In addition, walking, moderate to vigorous PA, and total PA significantly mediated the association between BMI and perception of better aesthetics (αβ = –.035, –.022, and –.071, respectively). Sedentary time was not a significant mediator of any associations between environmental factors and BMI. Conclusion: The association of several neighborhood environmental variables with BMI was partially mediated by PA in Nigerian adults. Including questions on specific types of sedentary behaviors in future prospective studies may improve understanding of the relative influence of sedentary behavior and physical activity on obesity control and prevention among sub-Saharan African adults.